Pengaruh Sudu - Sudu Pada Model Kincir Air Undershot Untuk Irigasi Pertanian - Abryan Rakasiwi; Rinaldi Rinaldi; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Undershot water wheel is appropriate technologies that raise the water level elevation of the river which was originally low for irrigation purposes with low cost. The water wheel is generally used in agricultural areas that do not get technical irrigation network. Water capacity capable be appointed the waterwheel is relatively low when compared with technical irrigation but the capacity could be increased if the factors affecting debits lifter of water can be optimized. These factors are the blades, the debit of flow, the position of box, the amount and type of box. The purpose of the research determines the dimensions of blade effective and debit of flow optimum which produces a maximum of debits lifter water. Research conducted in the laboratory to do the testing on the model undershot waterwheel. Model waterwheel was created in such a manner resembling a waterwheel in the field without scale models. Testing is done by varying the dimensions of the blade is the blade size of 6 cm × 4.5 cm, 6 cm × 6 cm and 6 cm × 7.5 cm, and then the flow rate is 3.07 l / sec, 3.8 l / sec and 5,99 l / sec and amount of box is 6, 12, 18, 24, 30 and 36 as well as the type of box that is type 1 (small size), type 2 (medium size) and type 3 (large size). The results showed the number of boxes 36 with a box type 3 in spoon size of 6 cm × 6 cm to debit of flow 5,99 l / sec produce maximum of debits lifter water that is equal to 38,17 ml /sec. It can be concluded dimention of spoon effective is the size of 6 cm × 6 cm and debit of flow that optimum is 5,99 l / sec.Keywords: undershot water wheel, dimension of blade, debit of flow